Brand Image and Purchase Decision: The Mediating Role of Product Quality and Social Media Engagement - Naili Rahma Yuliani; Sisno Riyoko; Mohamad Rifqy Roosdhani (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study examines the influence of brand image on purchase decision among Generation Z consumers who have purchased products at Corner Nyonya, with product quality and social media engagement as mediating variables. The background of the study is the growing importance of brand meaning, consumption experience, and digital interaction in shaping purchase decisions among young consumers. The objective of this research is to analyze both the direct and indirect effects of brand image on purchase decision. A quantitative explanatory approach was applied using a cross-sectional survey. Data were collected from 120 Generation Z respondents through a structured questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that brand image has a positive and significant direct effect on purchase decision. In addition, brand image significantly influences product quality and social media engagement, both of which also have significant effects on purchase decision. The mediation analysis indicates that product quality and social media engagement partially mediate the relationship between brand image and purchase decision, with social media engagement showing a stronger mediating role. The study concludes that brand image is translated into purchase decisions through experiential and digital pathways. Practically, culinary businesses targeting Generation Z should strengthen brand image, maintain consistent product quality, and optimize engagement-oriented social media strategies.